Dynamic proteome in enigmatic preeclampsia: an account of molecular mechanisms and biomarker discovery - Mary, Sheon; Patil, Gouri V.; Kulkarni, Asmita V.; Kulkarni, Mahesh J.; Joshi, Sadhana R.; Mehendale, Savita S.; Giri, Ashok P. (Proteomics Clinical Applications, 2012)
The coevolution of genomics and proteomics has led to advancements in the field of diagnosis and molecular mechanisms of disease. Proteomics is now stepping into the field of obstetrics, where early diagnosis of pregnancy complication such as preeclampsia (PE) is imperative. PE is a multifactorial disease characterized by hypertension with proteinuria, which is a leading cause of maternal and neonatal morbidity and mortality occurring in 5-7% of pregnancies worldwide. This review discusses the probable molecular mechanisms that lead to PE and summarizes the proteomics research carried out in understanding the pathogenicity of PE, and for identifying the candidate biomarker for diagnosis of the disease.
Keywords: Hypertension; Oxidative stress; Pregnancy complication; Proteinuria